Analysis of Influence of Masks Flow on Intake Valve of Gas and Oil Fuel Engine Based Simulation - Semin Semin; Mohammad Azzam Satriawansyah; Beny Cahyono; Nilam Sari Octaviani (Institut Teknologi Sepuluh Nopember, 2018)
Turbulent flow in the combustion chamber affects the combustion process which also affects the engine performance. The turbulent flow intensity can increase the duration of combustion, but too much turbulent turbulent flow leads to a tap. In addition, turbulent flow also contributes to the gas-water mixing process. There are two types of turbulent flow that occur inside the machine, which is a current vortex and a falling current. The current whirl is better known as the swirl flow and the falling current is better known as the tumble flow. The fluid flow in the combustion chamber can be adjusted by optimizing the engine components and developing the engine design. A review has been made of the vortex and Tumble flow on a luminous spark machine and its effect on turbulence and fire propagation. From several journals available to create tumble and swirl streams in the combustion chamber, they use modifications to the intake valve by adding vin to create a swirl stream and adding a mask to create a tumble stream. to know the experiment was successful or not, first modeling and then perform simulation using CFD Ansys Fluent. for the variables choose 3mask, 4mask, and 5mask (for addition of mask) which later dilih air flow formed by the addition of mask.